Awareness and Attitude of Farmers towards Agro-forestry (Indian Journal of Extension Education, 2015)
The study was conducted in Milkipur block of Faizabad District by concluding personal interview with 100 respondents selected through proportionate random sampling technique on the criteria of land holding size possessed, viz. Marginal, small, medium and large to find out the knowledge, attitude and adoption of agro-forestry systems. The majority of respondents (73 %) were found having medium level of attitude towards agro-forestry and attitude was measured on the scale developed by Shukla and Tyagi (2002). The respondents were categorized into three categories such as low, medium and high on the basis on the respondents e.g. low (up to 38), medium (39 to 44), high (45 and above) based on (i) mean-SD (ii) between mean ± SD (iii) mean +SD respectively. The correlation of attitude with like economic motivation and knowledge extent were found to be highly significant.